2017
DOI: 10.1007/s10561-016-9600-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple cycles of freeze–thawing on the RNA quality of lung cancer tissues

Abstract: RNA degradation is a major problem in tissue banking. We explored the effect of thawing flash-frozen biospecimens on the quality and integrity of RNA for genetic testing as well as for other cancer research studies. The histological quality of the frozen tumor sections was evaluated by using hematoxylin and eosin staining. RNA extraction from 60 lung cancer tissue samples subjected to various freeze/thaw cycles was performed using the RNeasy Plus isolation kit. RNA integrity was assessed by using an Agilent bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…While some studies claim RIN can be used to account for degradation effects in RNA-Seq 16 , others suggest it does not su ciently capture the effects of degradation on sample quality 26,28 . When directly observing the effect of freeze-thaw on RIN, studies have found a negligible effect 12 or can only detect an effect after numerous cycles 27,50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies claim RIN can be used to account for degradation effects in RNA-Seq 16 , others suggest it does not su ciently capture the effects of degradation on sample quality 26,28 . When directly observing the effect of freeze-thaw on RIN, studies have found a negligible effect 12 or can only detect an effect after numerous cycles 27,50 .…”
Section: Discussionmentioning
confidence: 99%
“…RIN-based metrics have known confounders such as transcript level, and thus have been called into question as an appropriate quality metric 26 . For example, RIN failed to indicate a decrease in sample quality in lung cancer tissue samples that underwent ve freeze-thaw cycles 27 and, in statistical analyses, failed to correct for the effects of degradation 28 . Despite this, many studies rely on RIN to correct for and assess sample quality confounders 16,29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that while noise increases with both decreasing RIN and increasing freeze-thaw, RIN may be an insu cient indicator of quality for samples that have undergone two or more freeze-thaws. Given these results, RIN may not always be a good metric to quantify the difference between technical replicates that have undergone variable sample handling 17,[26][27][28] . We validate noise by con rming that it does not change with input RNA concentration, excepting outliers (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S1). Given previous indications that these metrics may not su ciently address transcript degradation 17,[26][27][28] , we instead measure the introduction of noise to samples (Fig S2-3). We de ne noise as the fraction of reads in a sample that are randomly counted, rather than mapping to a sample-speci c gene.…”
Section: An Additional Freeze-thaw Cycle Increases Random Read Countsmentioning
confidence: 99%
“…Thermo Fisher Scientific instructions: Prepare a necessary amount of buffer by mixing QuBit DNA BR buffer solution with BR dye at a 200:1 ratio. RNA is particularly sensitive to degradation (Yu et al, 2017).…”
Section: Cell Homogenization and Lysismentioning
confidence: 99%